2019
DOI: 10.4103/jfmpc.jfmpc_168_19
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of obesity on QT-interval among adults

Abstract: Background: Obesity affects the different organ systems of human body and has been recognized as a risk factor for the development of many diseases. Most of the cardiovascular diseases develop due to obesity which reflects alterations in either cardiac morphology or conduction defects. These abnormalities are reflected in ECG as prolongation of various intervals. Prolongation of QT-interval has been found to be associated with ventricular arrhythmia and sudden cardiac death. Aims an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…These findings agreed with a retrospective cohort study showing that QTc prolongation occurs in COVID-19 patients treated with azithromycin and hydroxychloroquine, especially in the elderly, patients with BMI ≥ 30 kg/m 2 or with serum creatinine ≥ 1.5 mg/dL [ 24 ], The increase of QTc interval in the elderly might be caused by the physiological of the cardiovascular system and cardiac hypertrophy [ 25 ]. The prolongation of QTc interval with the elevation of BMI is believed to be caused by the increase of the cardiac output in individuals with high BMI, leading to subclinical cardiac hypertrophy [ 23 26 ]. Besides, Liu et al [ 27 ] found that the more the progression of the stage of chronic kidney disease, the higher the risk of QTc prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings agreed with a retrospective cohort study showing that QTc prolongation occurs in COVID-19 patients treated with azithromycin and hydroxychloroquine, especially in the elderly, patients with BMI ≥ 30 kg/m 2 or with serum creatinine ≥ 1.5 mg/dL [ 24 ], The increase of QTc interval in the elderly might be caused by the physiological of the cardiovascular system and cardiac hypertrophy [ 25 ]. The prolongation of QTc interval with the elevation of BMI is believed to be caused by the increase of the cardiac output in individuals with high BMI, leading to subclinical cardiac hypertrophy [ 23 26 ]. Besides, Liu et al [ 27 ] found that the more the progression of the stage of chronic kidney disease, the higher the risk of QTc prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Ожиріння вважається одним із основних факторів ризику серцево-судинних захворювань та серцевої недостатності (СН), підвищує ризик розвитку серцево -судинних порушень і раптової зупинки серця [1][2][3]. Серед факторів, що призводять до раптової серцевої смерті у осіб з надлишковою масою тіла, найчастіше зустрічаються різноманітні види аритмії на тлі структурних змін міокарду, в першу чергу дилятаційної кардіоміопатії, а саме подовження тривалості інтервалу QT, фібриляції передсердь, шлуночкової тахікардії та шлуночкової фібриляції [4,5].…”
Section: вступunclassified
“…A standard 12-lead ECG has numerous clinical applications, including screening for cardiac abnormalities in asymptomatic individuals, diagnosing and monitoring cardiac conditions, assessing response to treatment, guiding medical decisions, and evaluating perioperative risk in surgical patients. In the context of obesity, this condition may be associated with various ECG abnormalities [ 9 , 10 , 11 ]. ECG findings can provide valuable information for risk stratification, identifying potential complications, and guiding management strategies in obese individuals at risk for cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of the relationship between obesity and ECG findings is inconsistent across studies, showing conflicting results [ 12 , 13 , 14 , 15 ]. Until now, most commonly reported ECG findings in obese patients include increased heart rate, prolonged QT interval, increased QRS duration and R wave amplitude, and altered T wave morphology [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%